2016
DOI: 10.5665/sleep.6172
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict and Employee Sleep: Evidence from IT Workers in the Work, Family and Health Study

Abstract: Results highlight the unique associations of WTFC/FTWC with employee sleep independent of other work conditions and household and sociodemographic characteristics. Our novel methodological approach demonstrates differential associations of WTFC and FTWC with inconsistency of sleep timing. Given the strong associations between WTFC and poor sleep, future research should focus on reducing WTFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 41 publications
9
61
0
1
Order By: Relevance
“…Greater variability in WASO refers to greater irregularity in nighttime sleep quality, 21 which can be interpreted as a greater degree of daily fluctuation from his/her average sleep quality. Although longer WASO reflects poorer sleep quality, the person-level mean of WASO may indicate the individualized level of sleep quality (whether greater or lower).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Greater variability in WASO refers to greater irregularity in nighttime sleep quality, 21 which can be interpreted as a greater degree of daily fluctuation from his/her average sleep quality. Although longer WASO reflects poorer sleep quality, the person-level mean of WASO may indicate the individualized level of sleep quality (whether greater or lower).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, job titles were coded as core (=1; eg, software developers) vs noncore (=0; eg, technical support), following the practice in prior research. 21 In the IT firm, there was an organizational level merger and about half of employees had not yet received the intervention when merger was announced, whereas others had already received it. To take into account potential differences from this, we included an indicator for the event sequence between merger and intervention (0 = Intervention Premerger , 1 = Intervention Postmerger ) in our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Prior studies have shown that WFC is negatively associated with employees’ sleep quantity and quality. 10, 11 Most of these studies are cross-sectional and lacking the capacity to determine the causal direction between WFC and sleep. However, a few promising studies have also provided longitudinal evidence that WFC increases sleep problems.…”
Section: Introductionmentioning
confidence: 99%